Non-Fungible Tokens (NFTs) in Islamic perspective: challenges and way forward - Azlin Alisa Ahmad (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2024)
Non-fungible tokens (NFTs) have recently emerged as a novel application of blockchain technology in digital asset transactions. However, the integration of NFTs into Islamic finance remains limited due to several unresolved Shariah issues. This qualitative study employs content analysis to review past studies on NFTs from a Shariah perspective. The primary focus areas include the compliance of NFT transactions with the pillars of sale (bay'), the classification of NFTs as wealth (mal) in Islamic law, the use of cryptocurrency in NFT transactions, and the copyright protection of NFTs as digital assets. The key challenges identified encompass the lack of clear Shariah parameters governing NFT mechanisms, differences in scholarly opinions, the prevalence of ambiguity and uncertainty in NFT valuation and ownership, the high carbon footprint associated with NFT platforms, and inadequate legal protection for users. To facilitate greater adoption of NFTs in Islamic finance, this paper recommends the formulation of comprehensive Shariah parameters and guidelines, enhancement of transparency in royalty distribution, utilization of energy-efficient platforms, and the establishment of appropriate governance frameworks. Mainstreaming a Shariah compliant NFT ecosystem has the potential to drive innovation in Islamic fintech and the broader digital economy.